Primer registro de Leptopilina boulardi (Hymenoptera: Figitidae) asociado a Drosophila suzukii (Diptera: Drosophilidae) en el Alto Valle de Río Negro y Neuquén, Patagonia, Argentina - Garrido, Silvina A. (2018)
The larval endoparasitoid Leptopilina boulardi (Hymenoptera: Figitidae) is reported for the first time associated to Drosophila suzukii (Diptera: Drosophilidae) in raspberries and cherries crops at Alto Valle of Río Negro and Neuquén, being this the southernmost report in Argentina. Parasitoid diagnosis and prevalence are briefly commented.